Analisis AIDA Pada Iklan “Chery Omoda 5 ‘Great Performance With Premium Comfort’ Versi Youtube - Fauzan, Achmad; Christopher Yudha Erlangga (CV. ITTC INDONESIA, 2024)
With the development of technology or the new media era and currently there are many social media platforms that are in great demand by the public, for example YouTube, which is currently popular with people of all ages compared to television, this has become a big opportunity for business people or companies that easily promote their products in detail, one of the companies, namely Chery, is currently utilizing new media with the YouTube media platform to become a promotional platform to offer or promote in detail, starting from providing information about the exterior and interior shape of Chery products to providing information about the features they offer. given, then every content created by a businessman or company must understand how to create content that can attract attention and even consumers can have more confidence in the product being promoted, so this research discusses the content of Chery Omoda 5 advertisements using descriptive qualitative methods and approaches broadcast on YouTube .